1985
DOI: 10.1017/s0021932000015480
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and fertility in rural Bangladesh

Abstract: SummaryUsing a unique set of birth registration data from the Demographic Surveillance System of the International Centre for Diarrhoeal Disease Research, Bangladesh, for the period 1974–77, and socioeconomic information collected in the 1974 census, fertility was studied in relation to occupation, size of dwelling, number of cows and number of boats owned. The total fertility rate was found to vary between 6 and 6·5 except in the famine year of 1975. There was no consistent relationship between fertility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Recent empirically solid studies reveal socio-ecological correlates of differential reproductive success in humans (e.g., Ajami 1976;Boone 1988;Borgerhoff Mulder 1987b;Crook & Crook 1988;Essock-Vitale 1984;Faux & Miller 1984;Flinn 1986;Hughes 1986;Irons 1979;Kaplan & Hill 1985;Mealey 1985;Shaikh & Becker 1985;Stys 1957;Turke & Betzig 1985). Three general points emerge from these analyses:…”
Section: Introductionmentioning
confidence: 98%
“…Recent empirically solid studies reveal socio-ecological correlates of differential reproductive success in humans (e.g., Ajami 1976;Boone 1988;Borgerhoff Mulder 1987b;Crook & Crook 1988;Essock-Vitale 1984;Faux & Miller 1984;Flinn 1986;Hughes 1986;Irons 1979;Kaplan & Hill 1985;Mealey 1985;Shaikh & Becker 1985;Stys 1957;Turke & Betzig 1985). Three general points emerge from these analyses:…”
Section: Introductionmentioning
confidence: 98%
“…Of 4,743 dates given by parents, 21% fell on the 15th of the month; 41% fell on either the 10th, 15th or 20th of the month. Second, literacy and numeracy in this rural village were quite low at the time of the study (see Shaikh and Becker, 1985). Parents were unlikely to have checked daily for an event like tooth emergence and had they observed that a tooth emerged would have been unlikely, due to the high rate of illiteracy, to record the date with precision.…”
Section: Materials and Methods Subjectsmentioning
confidence: 96%
“…Generally, in rural areas, where access to resources is measured in terms of land ownership, the associations are positive (e.g. Chinese peasants of the 1930s: Lang, 1946; Polish peasantry after World War 11: Stys, 1957;Indian villagers: Driver, 1963; farmers in Punjab, Philippines and 15th century Tuscany: reviewed in Simon, 1974;Iranian villagers: Ajami, 1976; Brazilian and North American pioneers: Merrick, 1978; Javanese and Nepalese peasants: Nag, White & Peet, 1978; Bangladesh farmers: Shaikh & Becker, 1985). In other studies, particularly where access to resources is measured in terms of the husband's occupation, income or capital assets, the relationship between resources and women's reproductive success is less consistent.…”
Section: Previous Studiesmentioning
confidence: 99%